Five Emerging Neuroinvasive Arboviral Diseases: Cache Valley, Eastern Equine Encephalitis, Jamestown Canyon, Powassan, and Usutu - Gill, Christine M; Beckham, J David; Piquet, Amanda L; Tyler, Kenneth L; Pastula, Daniel M (Seminars in neurology, 2019)
There are many arthropod-borne viruses (arboviruses) capable of neuroinvasion, with West Nile virus being one of the most well known. In this review, we highlight five rarer emerging or reemerging arboviruses capable of neuroinvasion: Cache Valley, eastern equine encephalitis, Jamestown Canyon, Powassan, and Usutu viruses. Cache Valley and Jamestown Canyon viruses likely circulate throughout most of North America, while eastern equine encephalitis and Powassan viruses typically circulate in the eastern half. Usutu virus is not currently circulating in North America, but has the potential to be introduced in the future given similar climate, vectors, and host species to Europe (where it has been circulating). Health care providers should contact their state or local health departments with any questions regarding arboviral disease surveillance, diagnosis, treatment, or prevention. To prevent neuroinvasive arboviral diseases, use of insect repellent and other mosquito and tick bite prevention strategies are key.